Phylogenetically Older Introns Strongly Correlate With Module Boundaries in Ancient Proteins - Fedorov, Alexei; Roy, Scott; Cao, Xiaohong; Gilbert, Walter (Genome Research, 2003)
The hypothesis that some (but not all) introns were used to construct ancient genes by exon shuffling of modules at the earliest stages of evolution is supported by the finding of an excess of phase-zero intron positions in the boundary regions of such modules in 276 ancient proteins (defined as common to eukaryotes and prokaryotes). Here we show further that as phase-zero intron positions are shared by distant taxa, and thus are truly phylogenetically ancient, their excess in the boundaries becomes greater, rising to an 80% excess if shared by four out of the five taxa: vertebrates, invertebrates, fungi, plants, and protists.